Analysis of Frequency Selective with Nonlinear Antenna under Radiations of Bi-Frequency Waves Based on Genetic Algorithm (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
The more frequency radiation increases, the shorter becomes its wave length. The short wavelength, while hitting to some material, cause vibration and make change the positive and negative poles. As the most common way of genetic algorithm codification is using zero and one alphabet, genetic algorithm field is series of potential responses which are codified by some ways. Generally, the primitive population greatness has 30 or 100 members. In this study, genetic algorithm is applied for analyzing frequency selective surfaces with nonlinear antenna, in order to obtain two poles of nonlinear loads. It is worth to mention that two waves, with two different frequencies between 100 and 120 MHz, are radiated to antenna. The Ieq and Yin, in mentioned frequencies, are measured through FEKO software. Finally, after different analysis, it has been determined that in order to analyze selective surfaces, like harmonic balance, which are only capable of single frequency radiation, more global genetic algorithm analysis would be introduced for frequency selective surfaces.